Mentoring: A Faith Based Relational Leadership Approach in Preventing and Countering Violent Extremism in Kenya - Mbugua, Charles; Mang'eli, Sammy; Ragui, Mary (International Journal for Innovation Education and Research, 2019)
The article examines the role that mentoring, a critical relational leadership process would have in preventing and countering violent extremism by first examining the contexts of radicalization into violent extremism and past violent extremist attacks. Youths and adolescents in Kenya have been radicalized into violent extremism with resultant acts of terror that have resulted in; mass fatalities, casualties, destruction of facilities, disruption of livelihoods and business, and creation of immense fear within the public. The first major attack that seemed to have opened this cycle of al Qaeda and al Shabaab-led Jihadist attacks was the August, 1998 twin-bombing of the USA embassies in Kenya and Tanzania. Since then, we have had the advent of; al Qaeda, its affiliate al Shabaab, and ISIS attacks rising within the African continent with heavy impacts of death trails, casualties, and destruction. This year, Kenya has suffered a number of attacks targeting both soft and hard targets. Among the soft targets was the attack targeting Dusit Hotel in the upmarket 14 Riverside Complex, which left 21 Kenyans and foreigners dead. By extension there have been a number of IED attacks targeting the security services of Kenya many fatalities and casualties. All these attacks have been executed by violent extremists among who are Kenyan youth who have been recruited and radicalized into violent extremism as an ideology that is leveraged on the Islam religion. This ideology of Jihadism is skewed but uses narratives that easily appeal to those targeted for radicalization. Consequently there is an urgent need to have in place relevant mentoring leadership practice to enhance worldviews and perspectives among youth and adolescents which are in tandem with what a sane world subscribes to. It then becomes imperative to have a faith-based mentoring approach that is devoid of extremism and which gives the pool of those targeted a leadership component. This deliver a countering and preventive relational leadership model enhancing resilience of individuals and communities, while countering narratives and propaganda inherent in the recruitment and radicalization to violent extremism. Following literature review and conceptualization of the variables, this article concludes that preventive and countering violent extremism measures are best deployed first amongst the youth, who form the largest and most vulnerable pool of those targeted for radicalization due to; their crave for an identity, promises of a utopian caliphate on earth and life upon death, poverty, joblessness, presence of ungoverned spaces such as the complex cyber space, and dysfunctional social systems including families.
Journal Article
Keywords: Leadership; Jihadism.; Mentoring; Youths; Radicalization; Adolescents; Faith based organizations; Women; Collaboration; Violent extremism; Terrorism